Program Read Roamer at Mobile Library (ROOL) Untuk Meningkatkan Minat dan Literasi Membaca Siswa Sekolah Dasar - Nasori Efendi; Ida Yulianawati; Farah Fatihah Syaefudin (Universitas Negeri Gorontalo, 2024)
Reading interest and literacy skills play a crucial role in supporting effective learning processes among elementary school students. However, low reading interest remains a common challenge that hinders the development of reading habits and literacy competence at an early age. Therefore, innovative and engaging literacy programs are needed to foster a positive reading culture. The purpose of this study is to describe how the Read Roamer at Mobile Library (ROOL) program has improved students’ literacy and reading interest. The ROOL activity was conducted in collaboration with the Regional Library (Perpustakaan Daerah/PERPUSDA) at SDN 3 Balongan, Indramayu, under the theme Giving Young Learner Experiences to Explore the Universe. A descriptive method with a phenomenological approach was employed in this research. The participants consisted of 38 students from grades 1 and 2. Data were collected through direct observation during implementation of the program and interviews with four students selected randomly. The ROOL program was organized through three main activities: educational games, shared reading sessions, and storytelling activities, all designed to create a fun, interactive, and student-centered learning environment. The results show that after engaging in the ROOL activities, the students’ interest in reading significantly increased. This improvement was reflected in students’ increased enthusiasm, positive attitudes toward reading, active engagement during activities, and enjoyment in exploring various reading materials. Furthermore, students expressed a strong desire to participate in similar literacy activities in the future. As a conclusion, the Read Roamer at Mobile Library (ROOL) program has a positive impact on enhancing literacy and reading interest among elementary school students and possesses the capacity to function as an efficient and sustainable literacy program within the educational environment.